Oothu Chikitsa (Blowing Therapy)-A Review on Crisis Management in Snake Bites - Sharma, Swathi; Patil, Santosh F; Harish , Babu H; Namboodiri, Bramhadattan (International Research Journal of Ayurveda & Yoga, 2022)
Background: Snake bite management is one of the perplexing tasks in present day due to shortage of envenomation therapy. It is an emergency condition requiring quick acting remedy for different symptoms. Agada Tantra (toxicology) is one such branch of ayurveda which deals with the treatment principles of envenomation by animal or plant. Few empirical textbooks on Visha chikithsa of Kerala mention a therapeutic procedure ‘Oothu chikitsa’ (blowing therapy) to manage crisis of snake bite. Source: Literary review from the classical text. Indications: Classically the procedure is employed in snake bite victim presenting with diminished sensorium to both verbal and physical stimuli, by blowing a combination of drugs into the ears and over the scalp. This practice is still alive as a legacy at door-step of traditional practitioners of Kerala. Conclusion: Oothu chikitsa is feasible and effective in condition where patient is losing consciousness due to envenomation. These practices need to be explored and understood to improvise the management of envenomation and uphold its importance.